Integrating novel state of the art techniques into generic Personal Assistants with Home Assistant functionality - Thomas, FM; Juliana, R (International Journal of Computer Sciences and Engineering, 2025)
Software Personal Assistants (PA) have become the trademark of organizations which are involved in developing services that serve the digital needs of the public. Their aim through this trend is to integrate their core technologies into a single point of access in a user customized fashion using prediction mechanisms. Excluding circumstances where data has to be fetched or stored in online sources, most of the PAs existing in the market have a very local reach in its line of services. To enhance the reach of these services, we wish to integrate the functionalities of a Home Assistant (HA) to our PA such that users have the provision of controlling and monitoring devices in their homes amidst carrying out other PA functions in the Android Mobile Platform. The uniqueness in our PA lies in the usage of a Timestamp based Cipher primarily in the Chat Module and in other Modules that comprise of Cloud storage within our PA. Further, we introduce a novel HA Technology, that comprises of an Arduino and an ESP8266-01 Module, which performs the tasks necessary to provide the ambiance of a Smart Home. This Technology has the least investment necessary to set up the same up to date due to the simplicity of the hardware involved. The Smart Home will be powered by Internet of Things (IoT) which allows for the storage, retrieval and monitoring of data through the PA where the data corresponds to the states of the Smart Home at specific points of time.